Reducing bruising and pain through enhancement of subcutaneous anticoagulant injection techniques: a best practice implementation project. Issue 1 (18th March 2021) - Neo, Nicholas W.S.; Seow, Paola Y.Q.; Tho, Poh Chi
ABSTRACT: Introduction: Subcutaneous delivery of anticoagulant therapy is a common treatment modality across multiple medical disciplines. However, postinjection complications of bruising and pain continues to be a problem that has the propensity to affect patients physically and psychologically. A review of literature revealed a set of recommended injection techniques that have shown to improve these clinical outcomes. Objectives: The project aims to utilize an evidence implementation framework to introduce evidence-based injection technique, for the reduction of postinjection complications. Methods: A best practice implementation project was administered across three adult- cardiology and cardio-thoracic general wards in Singapore from March 2018 to February 2019. The Joanna Briggs Institute (JBI)'s framework of evidence implementation was utilized to enable change. A baseline audit was carried out to ascertain existing injection practices. Guided by the latest evidence, a new subcutaneous injection workflow was created and disseminated. Follow-up audits were held at 1 and 8-month postimplementation to assess compliance to the new subcutaneous injection workflow and the sustainment of change. Data were consolidated and analysed with the aid of JBI Practical Application of Clinical Evidence System. Barriers to change were also identified and addressed with the aid of JBI's Getting Research into Practice tool. Results: A large variation of subcutaneous injection techniques was observed at the baseline audit. At 1-month postimplementation, overall compliance with the new subcutaneous injection workflow was assessed to be 73.3%. Criteria 2 and 3 of the JBI Practical Application of Clinical Evidence System audit criteria improved from the baseline values (9.1–80%; 0–93.3%). At 8-month postimplementation, compliance rate remained high (83%) following strategies to reinforce and sustain change. Participants complied to Criteria 1 at all stages of the project. Correspondingly, the incidence of bruising reduced from baseline, with a relative risk reduction of 52% (1 month) and 29% (8 months). Median pain also decreased from the baseline, with an improvement from 2.0 (1.0–3.0) to 0.0 (0.0–1.0). Conclusion: Introduction and sustainment of change requires careful planning and execution. JBI's framework of evidence implementation is an effective model to guide this process. This project also highlighted the value of continuous learning, clinical update and practice standardization. This is especially important in the current climate of nursing mobility worldwide and the associated practice variations based on nursing education and experience.